Using of the phrasal verbs in the Little Prince of Antoine de SaintExupery. - Kokanova N; Khadjieva D.T (Genius Journals, 2022)
In this article, we will discuss the essence of Antoine de Saint-Exupery's The Little Prince and the use of phrasal verbs in the English translation of the work, their contribution and importance to the charm of the work. Even today, despite the fact that all the facilities for language learning have been created, testing English students about phrasal verbs is one of the main problems in understanding their meanings and using them correctly. This article is about increasing and strengthening the knowledge of phrasal verbs by learning phrasal verbs by reading books in English that are easier for language learners to understand and read, especially for beginners. The famous writer's work "Little Prince" is loved all over the world and is written in French. The article used an English translation of the book
Keywords: Phrasal Verb; Definition; Antoine De Saint-Exupery; Little Prince